Rapid synthesis of zeolitic imidazolate framework-8 (ZIF-8) nanocrystals in an aqueous system - Pan, Yichang; Liu, Yunyang; Zeng, Gaofeng; Zhao, Lan; Lai, Zhiping (Chemical communications (Cambridge, England), 2011)
We report here the first example of ZIF materials synthesized in aqueous solution. The synthesis was performed at room temperature and typically took several minutes compared to hours and days in non-aqueous conditions. The obtained product were ZIF-8 nanocrystals having size of ~85 nm and showed excellent thermal, hydrothermal and solvothermal stabilities.